Optimization of deployment of goods supply in high storage warehouse by means of the greedy algorithm - Sabo, Aleksandra (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2012)
A warehouse is one of the key areas in logistics. A large group of logistic problems is associated with the storage process. The optimization of logistic processes undoubtedly brings many benefits for businesses, both financial and organizational. This paper presents one of the most common problems which occurs in a specific type of warehouse – high storage warehouse. The problem is the location of the supply of goods in a high storage warehouse. Due to the large computational complexity of the problem, the paper proposes to use heuristic algorithms to solve the problem. The high storage warehouse is also a system that allows the comprehensive management of logistics operations in the warehouse by using information from a database and the corresponding data processing algorithms. The presented approach assumes the implementation of heuristic algorithms in the logistic warehouse management system and uses them in the high storage warehouse. This will allow the material management in the warehouse to become easier, faster and the decision-making to become more accurate.
Mathematical Economics, 2012, Nr 8 (15), s. 111-121
Keywords: traveling salesman problem; high storage warehouse; greedy algorithm